Early diagnosis and surgical treatment of primary cutaneous marginal zone B-cell lymphomas of the face in an Asian patient - Lee, Sam Yong; Kim, Woo Hyeong; Choi, Jun Ho; Kim, Kwang Seog; Hwang, Jae Ha (Archives of craniofacial surgery, 2021)
Primary cutaneous marginal zone B-cell lymphoma (PCMZL) is an uncommon type of malignant lymphoma that mainly occurs in the trunk and upper extremity, with less frequent incidence observed on the head. Herein, we report the early diagnosis and treatment of a rare case of facial PCMZL in an Asian patient. A 51-year-old man presented with masses on the forehead and nose tip, which he had incidentally discovered 2 months previously. The masses appeared as a papule on the forehead and a patch on the nose. There were no signs of infection or bleeding, and the patient reported no other symptoms. After complete surgical excision, PCMZL was diagnosed based on the permanent biopsy. The histopathological findings revealed lymphoid aggregations with multifocal granulomas. Further treatment and follow-up were conducted at the hematology and oncology department. Despite its rarity in Asian populations, cutaneous lymphoma should be included in the differential diagnosis of facial masses. Early diagnosis and treatment based on a physical examination, imaging study, and excisional biopsy are important for a favorable prognosis.